Pengaruh Tingkat Efisiensi Operasional terhadap Risiko Bisnis dan Dampaknya terhadap Kinerja Keuangan pada Perbankan yang Terdaftar pada Bursa Efek Indonesia Periode 2011-2014 - Nova Susanti (Jurnal Telaah dan Riset Akuntansi, 2015)
This study aims to examine the influence of operational efficiency on business risk. and to know the influence of operational efficiency and business risk on the financial performance simultaneously and partially on the Indonesian Banks listed on Stock Exchange Period 2011-2014. The study was conducted on the Indonesia Stock Exchange Period 2011-2014. Multiple linear regression was employed to analyze the data. The data analysis begins with a variable descriptive statistics, testing together and partial test and path analysis. The results also indicates BOPO and NIM can be used to predict the ROA. BOPO significance effect toward NIM. BOPO and NIM significance effect toward ROA. BOPO significance effect toward ROA via NIM on the banks listed on the Indonesia Stock Exchange.KEYWORDS :  BOPO, NIM and ROA